Rosja pisze własną historię. O bohaterach i wydarzeniach utrwalonych w aktach prawnych Federacji Rosyjskiej - Kuczyńska, Aleksandra (Doctrina. Studia społeczno-polityczne, 2019)
One of the most substantial question for the Russian Federation after 1991 there was relation between past and present. Some events and heroes from the past were not commemorated in the USSR historic policy and therefore people forgot about many of them. Similarly the international community tried to minimalized the imperial factors in the USSR historic policy. The USSR fall brought the real opportunity to celebrate the historic successful events and heroes. It took place epecially in the W. Putin’s presidency period. The main government politic purpose was to underline the positive events from the Soviet period because of joining all Russian tradition and create solidarity in Russian society. One of the most important thing was encoding Russian history in the national signs and symbols (anthem, flag, holidays) which remind Russian magnificence in the past and let her reconstruct her importance in the present time. Russians want to be proud of their own homeland, therefore they have written the history now.